Histoplasmosis of the small bowel in patients with AIDS. Issue 896 (1st June 2000) - Gumbs, Milton A; Girishkumar, Hanasoge; Yousuf, Arshad; Levy, Leo; Patel, Mayank; Narasimha, Vijay
Abstract : Two cases of jejunal strictures caused by Histoplasma capsulatum in AIDS patients are presented. Both patients were intravenous drug abusers. One patient, who was being treated for Pneumocystis carnii pneumonia, presented with jejunal perforation and the other presented with lower gastrointestinal bleeding and intestinal obstruction. On exploration, both patients were found to have jejunal strictures; one had intestinal perforation, and the other had intestinal obstruction with ulcers and strictures resulting in gastrointestinal bleeding. In areas where it is endemic, histoplasmosis is rarely disseminated. Dissemination is most commonly seen in immunosuppressed patients. Dissemination and extrapulmonary histoplasmosis is now included in the case definition of AIDS.